Study of AGC in Deregulated Environment using Different Three PID Structures - Sinha, Sayantan; Kumar Mallick, Ranjan; Kar, Devranjan (International Journal of Engineering and Technology, 2018)
The prime initiative of execution of the proposed work gives light to the restructured scenario of the current power sector and its associated load following issues. The focus of the work is mainly directed towards the AGC on an interconnected power system under restructured scenario. Each area focuses on the incorporation of renewable energy sources and therefore consists of a solar unit and a thermal unit as the generating sources. Three different structures of the conventional PID controllers have been taken into consideration for the secondary controller in AGC. The controller gains are optimized by a newly proposed Lightning search Algorithm. The analysis of the superiority of the system is done under two deregulated market scenarios i.e the base case and the bilateral transaction. The system is also subjected to random load changes in area 1 and the system performances under various controller structures are observed and analyzed.Â